2014
DOI: 10.1021/jz502351s
|View full text |Cite
|
Sign up to set email alerts
|

Optical Description of Mesostructured Organic–Inorganic Halide Perovskite Solar Cells

Abstract: Herein we describe both theoretically and experimentally the optical response of solution-processed organic−inorganic halide perovskite solar cells based on mesostructured scaffolds. We develop a rigorous theoretical model using a method based on the propagation of waves in layered media, which allows visualizing the way in which light is spatially distributed across the device and serves to quantify the fraction of light absorbed by each medium comprising the cell. The discrimination between productive and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
59
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 35 publications
4
59
0
Order By: Relevance
“…43 Because shiny metallic coatings are not 44 or cannot be 45 used for this purpose in all cases, and in order to extract conclusions that are as general as possible, we will not assume the presence of any specific type of contact. Also, for the sake of comparison, similar estimations like those reported in Figure 1 are shown in Figure S3 in the Supporting Information for a perovskite film of different optical constants, namely, like those reported in ref (41). …”
supporting
confidence: 75%
“…43 Because shiny metallic coatings are not 44 or cannot be 45 used for this purpose in all cases, and in order to extract conclusions that are as general as possible, we will not assume the presence of any specific type of contact. Also, for the sake of comparison, similar estimations like those reported in Figure 1 are shown in Figure S3 in the Supporting Information for a perovskite film of different optical constants, namely, like those reported in ref (41). …”
supporting
confidence: 75%
“…It should be also noted here that the highest efficiency for our perovskite tandem solar cells (around 25 %) is below Shockley-Queisser efficiency limit, which was however realized in some calculations [17][18][19][20][21][22] . The main underlying reason is that different electrical models and parameters are applied.…”
mentioning
confidence: 76%
“…However, despite their high performance, there are still two major issues that must be addressed. Firstly, a further improvement of the light collection of the PSCs should be achieved [6], [7]. Additionally, a reduction of the PSCs' toxicity [8], due to the presence of pure lead (Pb) in the perovskite materials, should be attained for their further commercialization.…”
Section: Introductionmentioning
confidence: 99%
“…Pathak et al [18] and Roopak et al [19] explored Mie theory [20] and showed that silver, gold and aluminum nanoparticles, embedded inside a perovskite matrix, support plasmonic resonances of high magnitude with tunable resonance frequency and width by varying the size, shape or material. These results are very promising since plasmonic nanoparticles can induce light incoupling to the perovskite near its band edge (~650-800 nm) where it shows inferior photo response due to lower absorption in conjunction with increased reflection from the perovskite at that regime [6], [7]. Moreover, Carretero-Palacios S. et al [21], [22] theoretically exploited the effect of plasmonic enhancement by incorporating metallic nanoparticles of different shapes, sizes, concentrations and composition in methyl ammonium lead iodide perovskite (CH3NH3PbI3) absorbing layers assumed to be supported on a glass substrate and coated by a hole transporting material.…”
Section: Introductionmentioning
confidence: 99%